Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's discuss whether functions [tex]\( m(x) \)[/tex] and [tex]\( n(x) = \frac{1}{4} x^2 - 2x + 4 \)[/tex] are inverse functions.
To determine if two functions are inverses, we need to check if they satisfy the following conditions:
1. [tex]\( m(n(x)) = x \)[/tex] for all [tex]\( x \)[/tex] in the domain of [tex]\( n \)[/tex].
2. [tex]\( n(m(x)) = x \)[/tex] for all [tex]\( x \)[/tex] in the domain of [tex]\( m \)[/tex].
### Step-by-Step Analysis:
1. Expression of [tex]\( n(x) \)[/tex]:
[tex]\[ n(x) = \frac{1}{4} x^2 - 2x + 4 \][/tex]
2. Finding the inverse candidate [tex]\( m(x) \)[/tex]:
- Assume [tex]\( n(x) = y \)[/tex]. Then we have:
[tex]\[ y = \frac{1}{4} x^2 - 2x + 4 \][/tex]
- We need to solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex].
3. Solving for [tex]\( x \)[/tex]:
- Set up the equation:
[tex]\[ y = \frac{1}{4} x^2 - 2x + 4 \][/tex]
- Rearrange and solve the quadratic equation for [tex]\( x \)[/tex]:
[tex]\[ \frac{1}{4} x^2 - 2x + (4 - y) = 0 \][/tex]
- Multiply through by 4 to clear the fraction:
[tex]\[ x^2 - 8x + 16 - 4y = 0 \][/tex]
- Rewrite the equation:
[tex]\[ x^2 - 8x + (16 - 4y) = 0 \][/tex]
- This is a standard quadratic equation in the form [tex]\( ax^2 + bx + c = 0 \)[/tex] where [tex]\( a = 1, b = -8, \)[/tex] and [tex]\( c = 16 - 4y \)[/tex].
4. Applying the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{64 - 4(1)(16 - 4y)}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{64 - 64 + 16y}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{16y}}{2} \][/tex]
[tex]\[ x = 4 \pm 2\sqrt{y} \][/tex]
- So, there are two possible solutions:
[tex]\[ x_1 = 4 + 2\sqrt{y} \][/tex]
[tex]\[ x_2 = 4 - 2\sqrt{y} \][/tex]
5. Verify inverse conditions:
- Substituting [tex]\( x = 4 + 2\sqrt{y} \)[/tex] or [tex]\( x = 4 - 2\sqrt{y} \)[/tex] into [tex]\( n(x) \)[/tex] to see if they satisfy [tex]\( n(m(x)) = x \)[/tex]:
- Substituting into [tex]\( n \)[/tex]:
[tex]\[ n(4 + 2\sqrt{y}) \quad \text{and} \quad n(4 - 2\sqrt{y}) \][/tex]
- Check if these yield [tex]\( y \)[/tex] when substited back.
6. Conclusion:
- After detailed checks and analysis, it turns out that neither of these candidates consistently satisfy both conditions [tex]\( m(n(x)) = x \)[/tex] and [tex]\( n(m(x)) = x \)[/tex] for all [tex]\( x \)[/tex].
Given our analysis, we conclude that:
The functions [tex]\( m \)[/tex] and [tex]\( n \)[/tex] are not inverse functions of each other. This is because there is no function [tex]\( m(x) \)[/tex] that satisfies both [tex]\( m(n(x)) = x \)[/tex] and [tex]\( n(m(x)) = x \)[/tex] for all [tex]\( x \)[/tex].
To determine if two functions are inverses, we need to check if they satisfy the following conditions:
1. [tex]\( m(n(x)) = x \)[/tex] for all [tex]\( x \)[/tex] in the domain of [tex]\( n \)[/tex].
2. [tex]\( n(m(x)) = x \)[/tex] for all [tex]\( x \)[/tex] in the domain of [tex]\( m \)[/tex].
### Step-by-Step Analysis:
1. Expression of [tex]\( n(x) \)[/tex]:
[tex]\[ n(x) = \frac{1}{4} x^2 - 2x + 4 \][/tex]
2. Finding the inverse candidate [tex]\( m(x) \)[/tex]:
- Assume [tex]\( n(x) = y \)[/tex]. Then we have:
[tex]\[ y = \frac{1}{4} x^2 - 2x + 4 \][/tex]
- We need to solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex].
3. Solving for [tex]\( x \)[/tex]:
- Set up the equation:
[tex]\[ y = \frac{1}{4} x^2 - 2x + 4 \][/tex]
- Rearrange and solve the quadratic equation for [tex]\( x \)[/tex]:
[tex]\[ \frac{1}{4} x^2 - 2x + (4 - y) = 0 \][/tex]
- Multiply through by 4 to clear the fraction:
[tex]\[ x^2 - 8x + 16 - 4y = 0 \][/tex]
- Rewrite the equation:
[tex]\[ x^2 - 8x + (16 - 4y) = 0 \][/tex]
- This is a standard quadratic equation in the form [tex]\( ax^2 + bx + c = 0 \)[/tex] where [tex]\( a = 1, b = -8, \)[/tex] and [tex]\( c = 16 - 4y \)[/tex].
4. Applying the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{64 - 4(1)(16 - 4y)}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{64 - 64 + 16y}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{16y}}{2} \][/tex]
[tex]\[ x = 4 \pm 2\sqrt{y} \][/tex]
- So, there are two possible solutions:
[tex]\[ x_1 = 4 + 2\sqrt{y} \][/tex]
[tex]\[ x_2 = 4 - 2\sqrt{y} \][/tex]
5. Verify inverse conditions:
- Substituting [tex]\( x = 4 + 2\sqrt{y} \)[/tex] or [tex]\( x = 4 - 2\sqrt{y} \)[/tex] into [tex]\( n(x) \)[/tex] to see if they satisfy [tex]\( n(m(x)) = x \)[/tex]:
- Substituting into [tex]\( n \)[/tex]:
[tex]\[ n(4 + 2\sqrt{y}) \quad \text{and} \quad n(4 - 2\sqrt{y}) \][/tex]
- Check if these yield [tex]\( y \)[/tex] when substited back.
6. Conclusion:
- After detailed checks and analysis, it turns out that neither of these candidates consistently satisfy both conditions [tex]\( m(n(x)) = x \)[/tex] and [tex]\( n(m(x)) = x \)[/tex] for all [tex]\( x \)[/tex].
Given our analysis, we conclude that:
The functions [tex]\( m \)[/tex] and [tex]\( n \)[/tex] are not inverse functions of each other. This is because there is no function [tex]\( m(x) \)[/tex] that satisfies both [tex]\( m(n(x)) = x \)[/tex] and [tex]\( n(m(x)) = x \)[/tex] for all [tex]\( x \)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.